Global Financial Stability Report, October 2014 : Risk Taking, Liquidity, and Shadow Banking: Curbing Excess while Promoting Growth. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
The October 2014 issue finds that six years after the start of the crisis, the global economic recovery continues to rely heavily on accommodative monetary policies in advanced economies. Monetary accommodation remains critical in supporting economies by encouraging economic risk taking in the form of increased real spending by households and greater willingness to invest and hire by businesses. However, prolonged monetary ease may also encourage excessive financial risk taking. Analytical chapters examine (1) the growth of shadow banking around the globe, assessing risks and discussing regulatory responses, and calling for a more encompassing (macroprudential) approach to regulation and for enhanced data provision; and (2) how conflicts of interest among bank managers, shareholders, and debt holders can lead to excessive bank risk taking from society's point of view, finding no clear relation between bank risk and the level of executive compensation, but that a better alignment of bankers' pay with long-term outcomes is associated with less risk.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet